Analysis of the growth kinetics of Fe2B layers by the integral method - Keddam M.; Kulka M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, an alternative approach based on the integral method was proposed to estimate the values of boron diffusion coefficients in the Fe2B layers grown at the surface of Armco iron. The set of differential algebraic equations (DAE) system was obtained to estimate the value of activation energy for boron diffusion when pack-boriding of Armco iron in the range of 1123 to 1273 K taking into account the boride incubation time. The present model has been validated by making a comparison between the experimental value of Fe2B layer thickness obtained at 1253 K for 5 h and the predicted results by using two different approaches. A good agreement was observed between these two set of data.